Additive‐Free Visible‐Light‐Mediated Hydro‐/Deuterodediazoniation of Arenediazonium Tetrafluoroborates in THF/THF‐d8. Issue 8 (9th July 2021) - Yang, Lian; Zhang, Cheng‐Pan
Abstract: A visible‐light‐irradiated reductive hydrodediazoniation of arenediazonium tetrafluoroborates in THF is described. The reaction proceeded at ambient temperature under catalyst‐ and additive‐free conditions to afford hydrodediazoniated products in good yields. This protocol was also suitable for deuterodediazoniation of arenediazonium tetrafluoroborates in THF‐d8, supplying the corresponding deuterated arenes in excellent yields. Advantages of this dediazoniation strategy include mildness, simplicity, visible‐light irradiation, a wide range of substrates, good functional group tolerance, with no use of catalysts and additives, and feasibility of a one‐pot diazotization/hydrodediazoniation process, which allows for a safe and convenient way to (deuterated)arenes from anilines. Abstract : Catalyst‐ and additive‐free decomposition of arenediazonium tetrafluoroborates in THF or THF‐d8 at ambient temperature under visible‐light irradiation afforded hydro‐/deuterodediazoniated products in good to excellent yields. The reaction features safety, simplicity, mildness, a wide range of substrates, good functional group tolerance, and a one‐pot diazotization/hydrodediazoniation process, allowing a direct, convenient deamination of anilines to (deuterated)arenes.